Viscoelasticity-Based Magnetic Resonance Elastography for the Assessment of Liver Fibrosis in Hepatitis C Patients after Liver Transplantation - Kamphues, C.; Klatt, D.; Bova, R.; Yahyazadeh, A.; Bahra, M.; Braun, J.; Klauschen, F.; Neuhaus, P.; Sack, I.; Asbach, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: Despite advantages in antiviral therapy of hepatitis C (HCV) in recent years, progressing liver fibrosis remains a major problem for patients suffering from hepatitis C after liver transplantation. Therefore, effective non-invasive methods for the assessment of liver fibrosis are needed in order to guide treatment decisions and predict prognosis in these patients. The aim of this study was to prospectively assess the diagnostic accuracy of viscoelasticity-based magnetic resonance (MR) elastography for the assessment of liver fibrosis in HCV patients after liver transplantation.Materials and Methods: After IRB approval, a total of 25 patients, who had received a liver graft due to chronic hepatitis C underwent both liver biopsy and MR elastography. Two viscoelastic constants, the shear elasticity μ and the powerlaw exponent α were calculated by fitting the frequency function of the complex shear modulus with the viscoelastic springpot-model.Results: A strong positive correlation between shear elasticity μ and the stage of fibrosis could be found (R = 0.486, p = 0.0136). The area under the receiver operating curve (AUROC) of MR elastography based on μ for diagnosis of severe fibrosis (F ≥ 3) was 0.87 and 0.65 for diagnosis of significant fibrosis (F ≥ 2). The powerlaw exponent α did not correlate with the stage of fibrosis.Conclusion: MR elastography represents a promising non-invasive procedure for the assessment of higher grades of fibrosis in HCV patients after liver transplantation. The poor correlation for lower grades of fibrosis suggests unknown mechanical interactions in the transplanted liver.
Keywords: transplantation; tissue characterization; surgery; fibrosis, liver; MR-imaging